Difusión del ecoperiodismo en los medios de comunicación de Quevedo y su impacto en la conservación del Medio Ambiente en la Parroquia San Cristóbal - Herrera Jiménez, Magaly Esther (2020)
Environmental journalism or Ecoperiodismo deals with information related to the environment and everything that is linked to impacts and modifications to the natural environment. It is the journalism that deals with obtaining and treating written, oral, audiovisual information, based on environmental issues. As well as the scientific, social, political, economic, cultural, environmental, and ethical aspects of them. Currently there are not many journalists in the canton who perform Ecoperiodismo, but the few that exist are looking for a space in some local media to inform citizens, and give advice on how to care for and maintain a healthy environment for future generations. With this research, the inhabitants of the San Cristóbal parish of the Quevedo canton will benefit, an action by which greater acceptance of care in the environment will be achieved, with an advance in conservation and a great increase in care. and hygiene of the sector, as an advance for improvements in the environment.